Screening for Significant Refractive Error Using a Combination of Distance Visual Acuity and Near Visual Acuity - Jin, Peiyao (PLoS One, 2015)
PURPOSE: To explore the effectiveness of using a series of tests combining near visual acuity (NVA) and distance visual acuity (DVA) for large-scale screenings for significant refractive error (SRE) in primary school children. METHOD: Each participant underwent DVA, NVA and cycloplegic autorefraction measurements. SREs, including high myopia, high hyperopia and high astigmatism were analyzed. Cycloplegic refraction results were considered to be the gold standard for the comparison of different screening measurements. Receiver-operating characteristic (ROC) curves were constructed to compare the area under the curve (AUC) and the Youden index among DVA, NVA and the series combined tests of DVA and NVA. The efficacies (including sensitivity, specificity, positive predictive value, and negative predictive value) of each test were evaluated. Only the right eye data of each participant were analysed for statistical purpose. RESULT: A total of 4416 children aged 6 to 12 years completed the study, among which 486 students had right eye SRE (SRE prevalence rate = 11.01%). There was no difference in the prevalence of high hyperopia and high astigmatism among different age groups. However, the prevalence of high myopia significantly increased with the age (χ² = 381.81, p<0.01). High hyperopia was the biggest SRE factor associated with amblyopia（p＜0.01，OR = 167.40, 95% CI: 75.14∼372.94). The DVA test was better than the NVA test for detecting high myopia (Z = 2.71, p<0.01), but the NVA test was better for detecting high hyperopia (Z = 2.35, p = 0.02) and high astigmatism (Z = 4.45, p<0.01). The series combined DVA and NVA test had the biggest AUC and the highest Youden Index for detecting high hyperopia, myopia, astigmatism, as well as all of the SREs (all p<0.01). CONCLUSION: The series combined DVA and NVA test was more accurate for detecting SREs than either of the two tests alone. This new method could be applied to large-scale SRE screening of children, aged 6 to 12, in areas that are less developed.